Energy Usage Analysis on The Production Process of Canned Crab Meat (Portunus pelagicus). Issue 1 (July 2020) - Hartulistiyoso, E; Akmal, M
Abstract: The energy usage anlaysis has been done on the production of canned crab meat ( Portunus pelagicus ). The analysis was based on the walktrough and detailed energy auditing at a canned crab meat production company located in Indramayu, Indonesia. It aims at obtaining the specific energy consumption used to produce canned crab meat and its saving opportunity. The result showed that the energy specific varied depending on the operated capacity, from 10.04 MJ/kg to 31.73 MJ/kg, with the evarage of 16.21 MJ/kg. The primary energy consumption were including diesel fuel 9.95 MJ/kg (61.4 %), electricity 5.91 MJ/kg (36.5 %), and human biological energy 0.34 MJ/kg (2.1 %). The largest energy was consumed at pasteurisation process, amounted 10.21 MJ/kg. Energy saving can be gained in amount of 5.38 MJ/kg of crabs if the process is running in full capacity using two pasteurization tanks.